Pengaruh Kompetensi dan Motivasi Terhadap Kepuasan Kerja Serta Berdampak pada Kinerja Karyawan di Hotel Sahid Jaya Solo - Alip Suroto; Soetomo WE; Hendrajaya Hendrajaya (Universitas Islam Nahdlatul Ulama Jepara, 2018)
This research was conducted at Hotel Sahid Jaya Solo which aims to analyse and describe the influence of competence and motivation on the performance of employees who are experiencing bad conditions because many of the competence of employees still as well as giving motivation is given less as the expectations of employees so turnover. Research data obtained through questionnaires and interviews. The sample used in this research is 114 respondents. The data obtained were processed by using descriptive analysis and quantitative statistical analysis. The result of regression analysis shows that the enhancement of competence and motivation on employee performance, and job satisfaction on the influence of competence and motivation will be followed by improvement of employee performance, and vice versa.